Thermodynamic Constraints on Electromicrobial Protein Production - Wise, Lucas; Marecos, Sabrina; Randolph, Katie; Hassan, Mohamed; Nshimyumukiza, Eric; Strouse, Jacob; Salimijazi, Farshid; Barstow, Buz (Frontiers in Bioengineering and Biotechnology, 2022)
Global consumption of protein is projected to double by the middle of the 21st century1. However, protein production is one of the most energy intensive and environmentally damaging parts of the food supply system today. Electromicrobial production technologies that combine renewable electricity and CO2-fixing microbial metabolism could dramatically increase the energy efficiency of commodity chemical production2-5. Here we present a molecular-scale model that sets an upper limit on the performance of any organism performing electromicrobial protein production. We show that engineered microbes that fix CO2 and N2 using reducing equivalents produced by H2-oxidation or extracellular electron uptake could produce amino acids with energy inputs as low as 64 MJ kg-1. This work provides a roadmap for development of engineered microbes that could significantly expand access to proteins produced with a low environmental footprint.